Hydrothermal carbonization as a preliminary step to pine cone pyrolysis for bioenergy production - Boutaieb, Mouzaina; Guiza, Monia; Román, Silvia; Ledesma Cano, Beatriz; Nogales, Sergio; Ouederni, Abdelmottaleb (Comptes Rendus. Chimie, 2020)
The main objective of this work was to elucidate the benefits associated with including hydrothermal carbonization (HTC) as the previous step to traditional fast pyrolysis of Tunisian pine cone (PC). The pyrolysis was performed in a fixed-bed reactor, while the HTC was carried out in an autoclave plus the subsequent carbonization step in the former reactor. The comparison of the two methods was based on the fraction yields, the molar composition of gas, the chemical composition, the surface characteristics, and the higher heating value.The pyrolysis of PC hydrochars (600 °C) was carried out using hydrochars prepared at various HTC temperatures (180–240 °C) and times (30, 60, and 180 min). Results showed that increasing the HTC temperature from 180 °C to 240 °C led to a decrease in the solid yield and an increase in the gas yield while increasing the HTC time led to a decrease in both solid and gas yields. The optimum HTC conditions (240 °C and 60 min) yielded a carbon content and a higher heating value of 92.5% and 34.28 MJ$· $kg$^{-1}$, respectively, producing a material that might be utilized as a category-A briquette for domestic use. Under these conditions, the gas production was also maximum.